Evaluation of the budbreak timing in walnut cultivars and breeding forms among the Kuban germplasm, and validation of the trait-related SSR-markers - I. I. Suprun; E. A. Al-Nakib; I. V. Stepanov; E. V. Lobodina; S. N. Shcheglov (Труды по прикладной ботанике, генетике и селекции, 2025)
Background. Walnut (Juglans regia L.) is the most widespread species within the genus Juglans. Late spring frosts can significantly reduce its yield. Development of cultivars that enter the growing season later helps to avoid the death of young buds. Earlier, during genetic studies, the SSR markers JRHR209732 and CUJRBO12 linked to the QTL of the “bud bursting time” character were identified. The objective of this study was to assess the budbreak timing in domestic cultivars and elite forms from the Krasnodar gene pool, as well as to test and validate the markers JRHR209732 and CUJRB012 linked to the locus controlling late bud bursting in walnut genotypes with relatively small differences in budbreak timing.Materials and methods. The material of the study included 32 elite breeding forms from the local gene pool, 3 domestic cultivars, and 2 cultivars of foreign origin. Phenological assessment of the budbreak time was carried out for three years (2022–2024). Genotyping of 35 accessions was performed using the SSR markers JRHR209732 and CUJRBO12. The sizes of PCR products of target marker alleles were assessed on a NANOPHOR 05 genetic analyzer.Results. Phenological assessment helped to identify accessions 17-5-5 and ‘Oven’ with the latest start of the growing season in three years of observations. Eight genotypes were classified as late in two seasons – they are also valuable for breeding. In 2023 and 2024, the budbreak was observed to occur earlier than in 2022. The effect of the mean monthly temperature in March played a decisive role in entering the phase when the budbreak started. Comparison of the SSR genotyping data with the results of the phenological assessment made it possible to reliably validate the allelic variants of the JRHR20973 and CUJRBO12 markers, characteristic of the accessions with early and late budbreaks among the walnut gene pool maintained in southern Russia.